Segmentation in Medical Image Processing - A Survey - Sivasamy, Jeevitha; Subashini, TS (International Journal of Computer Sciences and Engineering, 2025)
The main task of this work is to survey the various medical image segmentation methods analysed by researchers. Segmentation plays a crucial role in medical image processing. It is often used to pinpoint the objects and retrieve pertinent information in an image. Image is acquired with collection of objects having different intensities. The process of image segmentation is assessed through the different intensity level of the objects. Segmentation basically starts from threshold, histogram, clustering, edge based and many other methods. This paper analyses various medical image segmentation methods with their applications. Also it discusses with recent developments in segmentation techniques that are proposed for multiple diagnostic issues.